Pengembangan Jiwa Kewirausahaan Masyarakat Dalam Meningkatkan Kreativitas Pengolahan Gette’ (Keladi) di Desa Tuapejat Kecamatan Sipora Utara Kabupaten Kepulauan Mentawai - Hendra, Muhammad (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2024)
The aim of this activity is to provide students and business actors with an understanding of how to be creative in processing Gette' (Kaladi) so that it becomes a product that is varied and has high economic value. Socialization to students and business people regarding the importance of being creative in processing gette' (taro), and socialization on how to process gette' (taro). The activity carried out was to provide education regarding increasing creativity in the processing of Gette' (Kaladi). According to BPS data from Mentawai Islands Regency (2022), taro plant production reached 1041.5 tons. This production is supported by land that is very suitable for planting taro, because taro can grow in dry and swampy land. How to make subbet usually uses a mixture of banana and taro. You can use any type of banana or taro, but the most delicious are banana janang and taro sikobu. Subbets made from bananas are usually called subbet bagok and those made from taro are subbet gettek.